Snapshot photography : the lives of images - Zuromskis, Catherine (The MIT, 2013)
Snapshots capture everyday occasions. Taken by amateur photographers with simple point-and-shoot cameras, snapshots often commemorate something that is private and personal; yet they also reflect widely held cultural conventions. In this book, Catherine Zuromskis examines the development of a form of visual expression that is both public and private